Use of Stellarium to Prove Kepler's Third Law - Labibah, Haura; Prima, Eka Cahya; Fadzil, Hidayah Mohd (Jurnal IPA & Pembelajaran IPA, 2025)
This research aims to prove Kepler's third law with the application of stellarium. Stellarium provides information about planets, satellites and other celestial bodies. Observations were carried out from 5 31 May 2024. The data taken was angular distance in the Stellarium application. The objects observed were the four satellites of Jupiter which are often called the Galileo satellites. Jupiter's moon satellites include Io, Europa, Ganymede, and Callisto. Data is taken 20 times for 1 revolution. With adjusted observation time. Kepler's third law is proven in the case that the average distance of a planet raised to the power of three is directly proportional to the square of the planet's period of revolution.